2021
DOI: 10.3390/biomedicines9101412
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Effects and Pharmacokinetics of Active Compounds of Artemisia capillaris

Abstract: Artemisia capillaris Thunb. (A. capillaris, Yin-Chen in Chinese) is a traditional medicinal herb with a wide spectrum of pharmacological properties ranging from effects against liver dysfunction to treatments of severe cirrhosis and cancer. We used relevant keywords to search electronic databases, including PubMed, Medline, and Google Scholar, for scientific contributions related to this medicinal herb and the pharmacokinetics of its components. The pharmaceutical effects of A. capillaris contribute to the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 109 publications
0
13
0
Order By: Relevance
“…Among the various compounds present in these plants, terpenoids represent the main effective component. Modern pharmacological studies have shown that Artemisia medicinal plants exert diuretic, expectorant, antiinflammatory, hemostatic, hypotensive, and antiallergic effects ( Chen et al., 2021 ; Hsueh et al., 2021 ; Hong et al., 2022 ). Owing to their similar morphological characteristics and chemical composition, Artemisia species are often mixed or substituted in different regions of China.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various compounds present in these plants, terpenoids represent the main effective component. Modern pharmacological studies have shown that Artemisia medicinal plants exert diuretic, expectorant, antiinflammatory, hemostatic, hypotensive, and antiallergic effects ( Chen et al., 2021 ; Hsueh et al., 2021 ; Hong et al., 2022 ). Owing to their similar morphological characteristics and chemical composition, Artemisia species are often mixed or substituted in different regions of China.…”
Section: Introductionmentioning
confidence: 99%
“…Screening of active compounds of Artemisia capillaries , Gardeniae Fructus , Baicalin, Isatidis Radix , and Ganoderma from literature and Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP, https://tcmspw.com/index.phph), and met the standard of drug-likeness (DL) ≥ 0.18%. 17,4347 However, the value of oral bioavailability was not considered due to injection. Targets were then predicted from two sources: (1) TCMSP database; (2) Targetnet (http://targetnet.scbdd.com/), with prediction accuracy ≥ 0.7, predicted probability > 0.9.…”
Section: Methodsmentioning
confidence: 99%
“…com/index.phph), and met the standard of drug-likeness (DL) ≥ 0.18%. 17,[43][44][45][46][47] However, the value of oral bioavailability was not considered due to injection. Targets were then predicted from two sources: (1) TCMSP database; (2) Targetnet (http://targetnet.scbdd.com/), with prediction accuracy ≥ 0.7, predicted probability > 0.9.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Artemisia capillaris (AC) is a traditional oriental medicinal herb with various pharmacological activities, including hepatoprotective, cholestasis, analgesic, and antipyretic [ 13 , 14 , 15 ]. AC contains a variety of flavonoids, phenolic acids, terpenoids, coumarins, chlorogenic acid, ascorbic acid, scoparone, and essential oil, which promotes anti-oxidant, anti-inflammatory, anti-steatotic, anti-viral, and anti-tumor effects [ 16 ]. In particular, a recent study demonstrated that AC treatment ameliorated the severity of trinitrozobenzoic acid (TNBS)-induced colitis by inhibiting reactive oxygen species (ROS) generation and downregulating pro-inflammatory signaling pathways such as STAT3/MAPK/NF-κB [ 17 ].…”
Section: Introductionmentioning
confidence: 99%